1998
DOI: 10.1177/002224299806200204
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Price-Comparison Advertising on Buyers’ Perceptions of Acquisition Value, Transaction Value, and Behavioral Intentions

Abstract: The authors expand and integrate prior price-perceived value models within the context of price comparison advertising. More specifically, the conceptual model explicates the effects of advertised selling and reference prices on buyers’ internal reference prices, perceptions of quality, acquisition value, transaction value, and purchase and search intentions. Two experimental studies test the conceptual model. The results across these two studies, both individually and combined, support the hypothesis that buy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
534
2
21

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 779 publications
(578 citation statements)
references
References 42 publications
10
534
2
21
Order By: Relevance
“…An experimental approach was adopted, following the predominant methodology used in previous studies (see, e.g., Blair & Landon, 1981;Grewal et al, 1998;Urbany et al, 1988), although our final study might technically be termed quasi-experimental (Lord, 1994). Our choice of category types and discount sizes was informed by a prestudy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…An experimental approach was adopted, following the predominant methodology used in previous studies (see, e.g., Blair & Landon, 1981;Grewal et al, 1998;Urbany et al, 1988), although our final study might technically be termed quasi-experimental (Lord, 1994). Our choice of category types and discount sizes was informed by a prestudy.…”
Section: Methodsmentioning
confidence: 99%
“…By comparison, Urbany et al (1988) incorporated the notion of search benefit into their study, which they defined in the classic economic sense (after Stigler, 1961) as the improvement in value or price that the buyer believes can be found by searching. Purchase intention has been characterised as a willingness to buy a product (Compeau & Grewal, 1998;Grewal et al, 1998) and, similarly, the probability that a consumer will buy a product (Dodds, Monroe, & Grewal, 1991). In their meta-analysis, Compeau and Grewal (1998) reviewed a number of previous studies and confirmed that as the ARP increases or SP decreases, which would in turn tend to affect perceptions of acquisition and transaction value, then purchase intention increases.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to mulsumption phase. timedia presentations on a website, it is suggested that a map will give a richer and more detailed Comparing prices is often a key factor in decidpicture of the tourism product, especially if the ing which product to buy (Grewal, 1998) and product is a vacation package to a specific destinahence it is important to provide the customers with tion, but also if the customer is considering which services to support the need for information on travel options to consider on how to get to a destiprices and make the comparison as easy as possination. This need for deep and detailed informable for the customer.…”
Section: Phasementioning
confidence: 99%